The Effect Of Education On Self-Confidence And Self-Care In Type Ii Diabetes Mellitus Patients In The Working Area Of The Batujaya Karawang Community Health Center - Yanto Suryanto; Danur Azizah; Emi Pebriani; Ajeng Bela Dwi Pratiwi; Salma Salma (Utan Kayu Publishing, 2025)
Diabetes Mellitus (DM) is a chronic disease that requires long-term management through lifestyle modification and adherence to therapy. Health education is an essential intervention to improve patients’ self-efficacy and self-care in supporting lifelong treatment. Good self-efficacy enhances patients’ confidence in managing their condition, while optimal self-care contributes to improved quality of life. This study aimed to determine the effect of education on self-efficacy and self-care among patients with Type 2 Diabetes Mellitus in the working area of Batujaya Primary Health Center, Karawang. This research employed a quantitative approach with a quasi-experimental method using a one-group pretest–posttest design. The sampling technique used was proportional purposive sampling, involving 32 respondents. The instruments used were the Diabetes Management Self-Efficacy Scale (DMSES) and the Summary of Diabetes Self-Care Activities (SDSCA) questionnaire. Data were analyzed using the paired t-test. The results showed an improvement in self-efficacy and self-care after the educational intervention. Statistical analysis revealed a p-value of 0.000 for self-efficacy and 0.000 for self-care (p 0.05), indicating a significant effect of education on self-efficacy and self-care among patients with Type 2 Diabetes Mellitus. It is recommended that primary health centers optimize continuous health education, counseling, and health promotion programs to enhance patients’ ability to manage their condition and improve their quality of life